PENGEMBANGAN MEDIA TEKA TEKI SILANG TEMATIK UNTUK SISWA KELAS V SEMESTER I DI SDN 004 MERAL TAHUN PELAJARAN 2021/2022 - Tisrin Maulina Dewi; Fitria Meilina; Susi Irayanti Simanungkalit; Dirneti (JURNAL MINDA, 2022)
Some problems that can be formulated based on the disclosed background are: (1) Lack of media used in delivering material by classroom teachers. (2) The need for additional learning media. (3) In learning at this school the teacher is still focused on using handbooks, namely thematic books. (4) There are still many students who do not understand and respond during learning. (5) The TTS media has not yet been developed. This research is a research development or Research and Development (R&D) using the ADDIE model development method (Analysis, Design, Development, Implementation, Evaluation) which aims to develop learning tools. The population and sample were 39 students, then divided into three groups. In individual groups of 3 students, in small groups 9 students and limited groups of 27 students. This study uses the instrument that is interviews, observations and questionnaires. Then the research technique uses qualitative and quantitative data types. The results and discussion of the research to develop TTS media for fifth grade students at SDN 004 Meral, it can be concluded that: (1) In the results of the validation of the material expert's response to the feasibility of the content of the TTS media, that is, it is in accordance with the sub-components that get the average results. score 4.65. (2) The results of the validation of the media expert's response to the feasibility of the content of the TTS media are in accordance with the sub-components which get an average score of 4.3 in the very feasible category. (3) On the results of the validation of the homeroom teacher's responses for class V A, VB, VC SDN 004 Meral, it was stated that the TTS media to be developed had an average overall score of 4.01 which means it is feasible. (4) From the results of individual trials, small group trials and limited group trials by class V odd semesters at SDN 004 Meral, they have obtained appropriate criteria with an average score of 4.16. So that students are biased to use this TTS media as learning media Keywords: Development, Media Crossword, Thematic